CHILD HEALTH IN THE HEALTH CARE NETWORK: FROM CHILD CARE TO THE HOSPITAL ENVIRONMENT - Monique Alves Desidério, Bárbara; Estefani Silva Nascimento, Thalita; Petrúcia Medeiros de Miranda, Allana; Bianca Santos da Silva, Mariles; Junio do Nascimento, Francisco; da Silva Carvalho, Denise; Aparecida Tavares Fialho Bezerra, Maria; Carolina Salustino dos Santos, Maria (Health and Society, 2023)
The role of RAS in child health begins during pregnancy, considering aggravating factors and working to maintain the quality of life of the pregnant woman and the baby; passing through childcare, where potential pathologies must be identified and diagnosed, permeating, if necessary, medium and high complexity services; proceeding to treatment and continuous monitoring during all stages of childhood and, later, into adolescence and adult life.